Genetic Analysis of the Measles Virus From the Outbreaks in South Korea, 2019 - Kim, Jeong-Min; Park, Sehee; Kim, Sujin; Park, Kye Ryeong; Wang, Jin-Sook; Chung, Yoon-Seok (Frontiers in Microbiology, 2021)
Three genotypes (B3, D8, and H1) of the measles virus (MeV) have recently caused global outbreaks. In Korea, four measles outbreaks were reported during 2018–2019 and most patients were infants and health care workers in their 20s and 30s. To investigate the genetic characteristics and molecular epidemiology of the outbreaks, we analyzed the sequence of MeVs by targeting the N-450, MF-NCR, and/or H gene regions. Considering their phylogenetic relationships, besides the N-450 and MF-NCR sequences that are commonly used for genotyping MeVs, the MF-NCR-H sequence was related to MeVs. Phylogenetic clustering patterns reconstructed from the MF-NCR-H sequence set revealed that genotype D8 caused three of the four outbreaks, while B3 seemed to have induced the fourth outbreak. These results suggest that the MF-NCR-H sequence is useful for rapid confirmation of measles outbreaks and to identify the epidemiological routes of MeVs.